Efficiency analysis of catfish (Pangasius sp) marketing channels Balai Benih Ikan (BBI) Terantang - Susanto, Adha; Satriansah, Erman; Basriwijaya, Kiagus Muhammad Zain (Universitas Malikussaleh, 2024)
This study aims to analyze farmer's share, marketing margins, profit ratio, and marketing channel efficiency of catifish (Pangasius sp.) BBI Terantang in Sukamara and Balairiam District. The research method is a survey method by conducting direct observations and interviews. The data used were primary data and secondary data collected during September 2022 to June 2023. The data obtained was then analyzed using qualitative and quantitative descriptive analysis. The results showed that there were three types of marketing channels for BBI Terantang catfish, namely I: BBI Terantang and consumers, II: BBI Terantang, retailers, and consumers, and III: BBI Terantang, collectors, retailers, and consumers. Marketing channel I has a farmer's share value of 100%. The highest marketing margin occurred in marketing channel III with a total margin of Rp. 7,500.00-/kg. The profit ratio in marketing channels II and III benefits retailers and collectors with ratios of 7 and 3.3. As for the marketing efficiency of fresh catfish, all marketing channels are effective.Keywords: Catfish; Farmer's Share; Marketing Efficiency; Marketing Margin; Profit Ratio.